Quantitative In Situ Analysis of FoxP3(+) T Regulatory Cells on Transplant Tissue Using Laser Scanning Cytometry - Takahashi, Hidenori (2011)
There is abundant evidence that immune cells infiltrating into a transplanted organ play a critical role for destructive inflammatory or regulatory immune reactions. Quantitative in situ analysis (i.e. in tissue sections) of immune cells remains challenging due to a lack of objective methodology. Laser scanning cytometry (LSC/iCys) is a recently developed methodology that utilizes fluorescence-based quantitative measurements on tissue sections or other cellular preparations at a single-cell level. In this study, we have developed a novel objective method for analysis of immune cells, including Foxp3(+) T regulatory cell (T reg), on formalin-fixed / paraffin embedded (FFPE) transplant biopsy sections using LSC/iCys. The development of multiple immunofluorescent staining was established using FFPE human tonsil sample. The CD4/CD8 ratio and the population of T reg among CD4(+) cells were analyzed using LSC/iCys and compared with the results from conventional flow cytometry analysis (FCM). Our multiple immunofluorescent staining techniques allow obtaining clear staining on FFPE sections. The CD4/CD8 ratio analyzed by LSC/iCys was concordant with those obtained by FCM. This method was also applicable for liver, small intestine, kidney, pancreas and heart transplant biopsy sections and provide an objective quantification of T regs within the grafts.